PHYSICAL CULTURE AND HEALTH CULTURE - INNOVATIONAL CULTUROLOGICAL APPROACH - Grujo Bjeković; Branimir Mikić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Inaugural discusses of metatheoretical innovatinal forming of upgrading the cultural health and pedagogical technology of children's and youth's health progress and protection systems in the system of generally educational and health-school organizations. Establishment of a dynamical cumulative knowledge exchange and cooperative harmonization of the pedagogues of teaching obligations in the constitution of knowledge management educational space on rising health culture, physicality, and enriching sport and recreative lifestyle. Working out of con ceptual structural-functional scheme of health management measures in school and of evaluation of psychophysical and functional potentials, from the aspect of personalorientation. Establishment of complex system monitoring for physical development and physical capabilities and achieved results in domain of self-organized sport and sport-recreative selected activities.